Ghosts of the bluegrass - McCormick, James, 1935-; Wyatt, Macy, 1935- (University Press of Kentucky, 2009)
In Ghosts of the Bluegrass, James McCormick and Macy Wyatt present stories of Kentucky ghosts past and present. Some of the tales are set in rural areas, but many take place in urban areas such as the haunted house on Broadway in downtown Lexington and in buildings on the University of Kentucky campus, where Adolph Rupp is said to have conversed with the deceased biology professor Dr. Funkhouser. This volume contains chapters on haunted places, poltergeists, communication with the dead, and ghosts who linger to resolve unfinished business from their past lives, as well as a chapter about ghost.